PENERAPAN STRATEGI INKUIRI BIOLOGI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 010 SILIKUAN HULU KECAMATAN UKUI KABUPATEN PELALAWAN - Sungkem (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this research problem is the low science learning outcomes of third-grade students. This is characterized by the acquisition of an average value of 59.50 in science learning outcomes, with a student learning completeness percentage of 45%. Based on this, the researchers conducted classroom action research (PTK) with the aim to improve student learning outcomes through the implementation of biological inquiry strategies in science (IPA). This study was conducted in SD Negeri 010 Silikuan Hulu Kecamatan Ukui. The subjects were students of class III with a number of 15 students, with details of nine boys and six girls. The study was conducted over two cycles, consisting of 2 meetings and a daily test at the end of each cycle. Data collection techniques in this study included the observation technique for teacher and student activities and engineering tests, while the analytical technique used was descriptive analysis of activity data and the results of teachers and students learning science. Research suggests that the application of biology inquiry strategies can improve learning outcomes in science (IPA). This is evidenced by: (a) the activities of teachers and students increasing in each cycle. The activities of teachers in the first cycle, the first meeting, obtained a percentage of 42%, and the first cycle of meetings both gained 52%. The first meeting of the second cycle gained 65%, and in the second meeting of the second cycle, 78% was obtained. Activities of students in the first cycle, the first meeting, obtained a percentage of 49%, student activities at the second meeting I silus 61%, and the second cycle first meeting obtained a percentage of 68%, and the second cycle's second meeting obtained a percentage of 81%. (b) the results of the students' learning experience at each cycle. Before the action, student learning was complete by 45% with an average value of 59.50. The first cycle increased to 72% with an average value of 64. The second cycle increased to 90% with an average of 68.